2018
DOI: 10.1186/s13287-018-1044-5
|View full text |Cite
|
Sign up to set email alerts
|

A review: therapeutic potential of adipose-derived stem cells in cutaneous wound healing and regeneration

Abstract: As the most important barrier for the human body, the skin often suffers from acute and chronic injuries, especially refractory wounds, which seriously affect the quality of life of patients. For these refractory wounds that cannot be cured by various surgical methods, stem cell transplantation becomes an effective research direction. As one of the adult stem cells, adipose-derived stem cells play an indispensable role in the repair of skin wounds more than other stem cells because of their advantages such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 62 publications
0
100
0
Order By: Relevance
“…Commercial human ASC HMEC Stimulation of vessel-like structure formation [73] Human sub-cutaneous adipose tissue obtained from healthy females (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years old).…”
Section: Asc Source Model Effect Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Commercial human ASC HMEC Stimulation of vessel-like structure formation [73] Human sub-cutaneous adipose tissue obtained from healthy females (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years old).…”
Section: Asc Source Model Effect Referencementioning
confidence: 99%
“…Of note, the adipose tissue contains higher densities of adult MSCs compared to bone marrow [21,22]. The abundance and accessibility of ASCs together with their multilineage differentiation potential as well as their immunomodulatory properties [23,24] also make them promising candidates for non-healing wound treatment [25][26][27][28][29][30]. However, there are still unresolved critical issues for the definition of effective ASC therapy, which include, among others, the need to standardize methods of isolation, culture, expansion, and characterization of ASCs as well as appropriate quality and safety control for cell-based therapies [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high therapeutic potential, ASCs are now considered an indispensable tool in regenerative medicine [61][62][63][64]. Studies have shown the successful treatment with ASCs for many disease including graft-versus-host disease [65], wound healing [66], cardiovascular [67], inflammatory bowel disease [68], diabetes mellitus [69] and several injuries including kidney and spinal cord [70], bone and craniofacial reconstruction [71,72], liver cirrhosis [73], multiple sclerosis [74]. In addition to their self-renewal ability, ASCs have the ability to differentiate into multiple lineages, including adipocytes, osteoblasts, chondrocytes, and endothelial cells [75,76].…”
Section: Is There a Role Of Adipose-derived Stem Cells (Asc) In Lipedmentioning
confidence: 99%
“…36,37 In addition, this growth factors not only regulate epithelial regeneration through paracrine matrix-epithelial interaction, but regulate epithelial regeneration through direct interaction of growth factors with cognate receptors in the epidermis. 38 The secretion of EGF and PDGF protein from BTECs in each group was measured by ELISA assay and presented in Fig. 11.…”
Section: Epidermal Growth Factor (Egf) and Platelet Derived Growth Famentioning
confidence: 99%